The Human Factor in AI-Based Decision-Making - Meissner, Philip; Keding, Christoph (MIT Sloan Management Review, 2021)
Individuals' unique decision-making styles inform the choices they make when working with AI-based inputs. The authors explain how organizations can optimize AI and overcome flaws in human judgment by identifying and understanding the three types of decision maker: skeptics, interactors, and delegators. They also offer three strategies for integrating AI into organizational decision-making processes.
Online resource; Title from title page (viewed October 12, 2021)
Keywords: Artificial intelligence; Business -- Data processing; Business -- Technological innovations; Artificial Intelligence; Intelligence artificielle; Gestion; Informatique; Affaires; Innovations; artificial intelligence; Business; Data processing; Business; Technological innovations